Study of malaria and associated co-morbidity in children admitted with fever manifestation in a tertiary care centre - Ghanghoriya, Pawan; Borkar, Rahul; Lazarus, Monica; Ajmariya, Manish (International Journal of Contemporary Pediatrics, 2020)
Background: Children under five year of age are highly vulnerable to malaria infection and often face dire consequences such as severe malaria if they are not promptly and adequately treated with anti-malarial medications. Authors set out to evaluate malaria and associated co-morbidity among children admitted with febrile illness in tertiary care center NSCB Medical college Jabalpur, India. Methods: This prospective and analytic study focused on children admitted with fever in pediatric unit of N.S.C.B. Medical College, Jabalpur, Madhya Pradesh, India. If any co-morbidity present with malaria their manifestation was noted. Association of co-morbidity with malaria was done, and effect of co-morbidity on severity of malaria and outcome of patients was noted. Results: A total number of 1950 of children suspected to have malaria who were tested by RDT and microscopy (PSMP), out of them 100 children were positive. Mean age calculated was 7.3±4.3 years. Maximum number of severe malaria cases (40.6%) were found in 6 months to <5 years age group. Most common co-morbidity associated with malaria was anemia (53%) followed by pneumonia (36%) hepatitis (26%), diarrhea (24%), enteric fever (15%), septicemia and meningoencephalitis (10%) each, UTI (4%), and AKI (6%), while dengue (3%) and severe acute malnutrition (2%). Out of 69 cases of severe malaria 46.3% cases had two and 34.7% cases had more than two co-morbidities while in 31 cases of uncomplicated malaria 38.7% cases had two co-morbidity and only 3% had more than two co-morbidity. Conclusions: All RDT positive cases have associated co-morbidity with malaria in our study, more is the co-morbidity is longer were the duration of stay and higher the complications and even mortality.